Coupling of N‐Doped Mesoporous Carbon and N‐Ti3C2 in 2D Sandwiched Heterostructure for Enhanced Oxygen Electroreduction. Issue 15 (28th February 2022) - Gou, Zhaolin; Qu, Huiqi; Liu, Hanfang; Ma, Yiru; Zong, Lingbo; Li, Bin; Xie, Congxia; Li, Zhenjiang; Li, Wei; Wang, Lei
Abstract: 2D heterostructures provide a competitive platform to tailor electrical property through control of layer structure and constituents. However, despite the diverse integration of 2D materials and their application flexibility, tailoring synergistic interlayer interactions between 2D materials that form electronically coupled heterostructures remains a grand challenge. Here, the rational design and optimized synthesis of electronically coupled N‐doped mesoporous defective carbon and nitrogen modified titanium carbide (Ti3 C2 ) in a 2D sandwiched heterostructure, is reported. First, a F127‐polydopamine single‐micelle‐directed interfacial assembly strategy guarantees the construction of two surrounding mesoporous N‐doped carbon monolayers assembled on both sides of Ti3 C2 nanosheets. Second, the followed ammonia post‐treatment successfully introduces N elements into Ti3 C2 structure and more defective sites in N‐doped mesoporous carbon. Finally, the oxygen reduction reaction (ORR) and theoretical calculation prove the synergistic coupled electronic effect between N‐Ti3 C2 and defective N‐doped carbon active sites in the 2D sandwiched heterostructure. Compared with the control 2D samples (0.87–0.88 V, 4.90–5.15 mA cm −2 ), the coupled 2D heterostructure possesses the best onset potential of 0.90 V and limited density current of 5.50 mA cm −2 . Meanwhile, this catalyst exhibits superior methanol tolerance and cyclic durability. This design philosophy opens up a new thought for tailoring synergistic interlayer interactions between 2D materials. Abstract : The atomic‐level coupling structure of N‐doped defective carbon and N‐Ti3 C2 (DC/N‐Ti3 C2 ) in 2D sandwiched heterostructure is fabricated via F127‐polydopamine composite micelle self‐assembly followed by ammonia annealing treatment. With the fine tailoring of heterointerface interactions and optimized electronic bandgap, the DC/N‐Ti3 C2 electrocatalyst suggests enhanced activity and durability in alkaline media toward the oxygen reduction reaction.